The interplay between magma source and geodynamic evolution in porphyry Cu-Au fertility of the Farallon Negro Volcanic Complex, Argentina - Ince, Madeleine (2023)
Zircon U-Pb, O, Lu-Hf and trace element systematics are used to track the magmatic-hydrothermal evolution and metallogenic potential of porphyry intrusions and associated Cu-Au deposits. We apply this analytical approach to unveil the poorly constrained geological history of the Farallon Negro Volcanic Complex in the Central Andes of northwest Argentina. This complex contains the world-class Au-rich Cu-Au Bajo de la Alumbrera deposit (heredated at 6.9 ± 0.1 to 6.8 ± 0.2 Ma; U-Pb SHRIMP) and a series of barren to weakly mineralized satellite porphyry intrusions, including El Durazno (8.0 ± 0.3 Ma; U-Pb SHRIMP), San Lucas (7.4 ± 0.1 to 7.3 ± 0.1 Ma; U-Pb SHRIMP) and Las Pampitas (7.2 ± 0.2 to 7.0 ± 0.1 Ma, U-Pb SHRIMP). Zircon Hf and O isotope data record a change in magma source from El Durazno (δ18O = 5.7 ± 0.3‰; εHf = 0.3 ± 1.8) to San Lucas, Las Pampitas and Bajo de la Alumbrera (δ18O > 6.7‰, εHf = 4.0 ± 0.5 to 2.2 ± 1.0). This reflects a switch from a predominantly mantle-derived magma source to a mixed mantle-derived and supracrustal source that homogenized in a lower-crustal magma assimilation, segregation and homogenization (MASH) zone. All intrusions have a hydrous (Eu/Eu* > 0.5, Dy/Yb < 0.3), oxidized (ΔFMQ >1.0, Ce/Ce* > 100) and, therefore, ‘fertile’ zircon trace element signature, despite having variable Cu and Au grades. Likewise, ore-barren extrusive units in the FNVC have an overlapping ‘fertile’ zircon signature, reinforcing the view that zircon-based proxies for fertility may not be useful for mineralization targeting at a district scale. The magmatic evolution of the FNVC was significantly influenced by the tectonic setting, as the onset of regional transpression at ~8 Ma after a period of localized extension caused pooling of mantle-derived magmas in a lower-crustal MASH zone and build-up of volatiles and metals. The petrogenetic model proposed for the FNVC emphasizes the role of the geodynamic environment and magma evolution in the Cu-Au endowment of Bajo de la Alumbrera.